Developing an efficient discus model - Maynard, M. (Track Coach, 2016)
The discus throw allows for a wide range of individual expression of the technical fundamentals. Current successful technical expressions of the discus cover a wide variety of styles and philosophies of throwing. The physical parameters of successful discus throwers, on the world stage, indicates the necessity for well above average size. For example, world class male discus throwers tend to be about 1.95m/ 115kg (6-4¾/254lbs.). However, exceptions to these physical parameters readily exist on both the national and world levels. The athletes who comprise these exceptions typically compensate for physical deficits with a particularly exceptional specific physical talent(s), and/or an exceptionally well-adapted technical model. The dynamic nature of the discus movement has historically witnessed a variety of successful technical expressions. Many of these utilize large and sweeping movements to accomplish mechanical advantage within the throw. Those technical models will continue to be successful. The technical model should seek to maximize the athlete's particular physical attributes (i.e., system of levers, range of movement, biomotor capabilities). The technical model to be presented and discussed in this article is meant to pare down the movements of the discus thrower to a bare and essential minimum.